Urbanisation and the loss of phylogenetic diversity in birds - Daniel Sol; Ignasi Bartomeus; César González‐Lagos; Sandrine Pavoine (Ecology Letters, 2017)
Despite the recognised conservation value of phylogenetic diversity, little is known about how it is affected by the urbanisation process. Combining a complete avian phylogeny with surveys along urbanisation gradients from five continents, we show that highly urbanised environments supported on average 450 million fewer years of evolutionary history than the surrounding natural environments. This loss was primarily caused by species loss and could have been higher had not been partially compensated by the addition of urban exploiters and some exotic species. Highly urbanised environments also supported fewer evolutionary distinctive species, implying a disproportionate loss of evolutionary history. Compared with highly urbanised environments, changes in phylogenetic richness and evolutionary distinctiveness were less substantial in moderately urbanised environments. Protecting pristine environments is therefore essential for maintaining phylogenetic diversity, but moderate levels of urbanisation still preserve much of the original diversity.